Postharvest physiochemical responses of cut rose (Rosa hybrida L.) to antitranspirant and vacuum cooling. - Song, Xiaoyong; Wang, Weishu; Zhang, Chuan; Ma, Qiang; Li, Yunfei (2011)
A study was conducted to examine the postharvest physiochemical responses of cut rose (Rosa hybrida L. cv. First Red) to antitranspirant spraying and vacuum cooling. Vase life, flower opening index, stomatal conductivity, transpiration rate, weight change and malondialdehyde (MDA) content were measured. Compared with the control, spraying antitranspirant alone (WV) could reduce the degree of fresh weight loss, delay the process of flower opening, slow down the rate of stomatal conductance reduction, decrease water loss during transpiration, maintain the integrity of cell membranes, reduce the accumulation of MDA and prolong the vase life of cut roses. The combination of antitranspirant and vacuum cooling could more effectively improve the preservation of cut roses with a vase life 52%-70% longer than that of roses in the control group. The vase life of antitranspirant-sprayed roses before vacuum cooling (WVV) was the longest, 12% longer than that of vacuum-cooled roses before antitranspirant application (VWV). This research should provide a way to extend the vase life of cut flowers for growers and the cutflower industry.
Keywords: Rose culture; Chemical properties; Postharvest handling